IPB University's Strategic Capabilities Dealing with Environmental Turbulence - Agustina Widi (Jurnal Ilmu Manajemen & Ekonomika, 2023)
The turbulent environmental conditions in the education industry urgently require a flexible strategic response and strong organizational capabilities. Universities cannot be left behind with their practices which tend to be planned, slow and bureaucratic. The purposes of this study include analyzing the turbulence level of the higher education environment, assessing the condition of IPB University's organizational capabilities, and designing IPB University's strategy based on the value of organizational capability and the level of environmental turbulence. The method used in this study is a qualitative method and sample selection is done by purposive sampling method. The study results show that progressive turbulence in the higher education environment demands service improvements to anticipate customer developments. The capability of IPB University must be continuously encouraged to fit the level of environmental turbulence to gain competitive advantage.